Northern Norway Sporophytes of Saccharina latissima Display Distinct Gene Expression Profiles in Response to Temperature and Photoperiod - Martin Bua Rønhovde; Catia Monteiro; David Dolan; Kjersti Sjøtun; Håkon Dahle (Ecology and Evolution)
ABSTRACT Sugar kelp (Saccharina latissima) is an ecologically and increasingly economically important kelp, distributed from temperate to Arctic rocky shores. However, S. latissima is presently threatened by ongoing climate changes. Genetic variations have previously been identified across S. latissima populations. However, little is known regarding the genetic basis for adaptation and acclimation to different environmental conditions. In this study, a common garden experiment was performed with sporophytes originated from North‐Norway (NN), Mid‐Norway (MN), and South‐Norway (SN), representing areas with highly different temperatures and photoperiods. Transcriptomic analyses revealed significant variation in the gene expression of cultures from North‐Norway, associated with low temperature and long photoperiods, compared to Mid‐ and South‐Norway. Differentially expressed genes included genes linked to photosynthesis, chlorophyll biosynthesis, and heat response, suggesting that they are directly involved in temperature and light adaptation. In addition, genes related to growth, metabolism, protein synthesis, and translation were upregulated in the NN genotype, providing evidence that the NN genotype is better adapted to low temperatures than the SN and MN genotypes. Significant variation in gene expression among populations found in this study is influenced by the environment, but genetic differentiation by origin seems to play a role as responses were population specific. This study provides a baseline for deeper insight into the local adaptation potential of S. latissima populations along the Norwegian Coast with implications for the conservation of natural populations.